2023
DOI: 10.1186/s40001-023-01036-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for pressure injuries in patients who have undergone vascular operations: a scoping review

Abstract: Background Patients who have undergone vascular operations are thought to be at an increased risk for developing pressure injuries; however, the extent to which pressure injuries occur in this population is not clear. This scoping review sought to summarize what is known about the incidence of pressure injuries, and the risk factors for the development of pressure injuries in patients who have undergone vascular operations. Main An initial search i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A recent scop-ing review found that the incidence of PIs in these patients ranged from 17.2% to 45%, and varied according to procedure. 1 The 2018-2019 International Pressure Ulcer Prevalence (IPUP) Survey of 296,014 acute care patients determined a 6.3% prevalence rate for critical care surgical patients (n = 5,367) and 6% for critical care cardiac patients (n = 5,385). 4 Since the IPUP Survey did not include a classification for cardiothoracic surgery patients, no prevalence rate for these patients could be derived from this study.…”
Section: Evaluating the Eff Ectiveness Of An Alternating Pressure Ove...mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent scop-ing review found that the incidence of PIs in these patients ranged from 17.2% to 45%, and varied according to procedure. 1 The 2018-2019 International Pressure Ulcer Prevalence (IPUP) Survey of 296,014 acute care patients determined a 6.3% prevalence rate for critical care surgical patients (n = 5,367) and 6% for critical care cardiac patients (n = 5,385). 4 Since the IPUP Survey did not include a classification for cardiothoracic surgery patients, no prevalence rate for these patients could be derived from this study.…”
Section: Evaluating the Eff Ectiveness Of An Alternating Pressure Ove...mentioning
confidence: 99%
“…PIs are defined as damage to the skin and underlying soft tissue, usually occurring over bony regions of the body, and are classified into four stages based on severity. 1,2 Stage 1 indicates a nonblanchable redness of the skin, with staging progressing to stage 2 (partial loss of skin), stage 3 (full-thickness skin loss), and stage 4 (full-thickness skin and tissue loss). 2 In a study by Alderden and colleagues that included 4,934 critical care patients who presented to the hospital with no preexisting PIs, 7% (n = 352) developed a HAPI; additionally, 50% of the stage 1 HAPIs worsened into more severe stages, although the study does not indicate the stages reached.…”
Section: Evaluating the Eff Ectiveness Of An Alternating Pressure Ove...mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, BMI, height, weight, nutritional status and other indicators were mostly used to assess the risk. [19][20][21][22][23] Based on the theoretical framework of the study, this study adopted objective measurement tools to explore the risk factors from the perspective of the pathogenesis of IAPI, and also provided basis for the accurate assessment of IAPI in the future.…”
Section: Outcome Measuresmentioning
confidence: 99%